Knowledge of Agricultural Officers on sustainable agricultural practices: a micro study in Guntur district of Andhra Pradesh - K.Guruva Reddy,; P.Punna Rao, (Journal of Agricultural Extension Management, 2025)
Sustainable agriculture is that form of farming which produces sufficient food to meet the needs of the present generation without eroding the ecological assets and the productivity of the life supporting system of future generations (Venkataramani, 1991 )